1989
DOI: 10.1164/ajrccm/140.5.1463
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines and Epidermal Growth Factor in Monocrotaline-induced Pulmonary Hypertension

Abstract: Multiple lines of evidence suggest that the polyamines, a family of low-molecular-weight organic cations with documented regulatory note in cell growth and differentiation, are involved with hyperplastic and hypertrophic responses of lung cells underlying hypertensive pulmonary vascular disease. Little is known, however, of the factor(s) initiating polyamine synthesis in pulmonary hypertension. This study tested the key aspects of the hypothesis that augmented polyamine synthesis, and attendent vascular struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Several growth factors, including EGF, PDGF, and TGF-β1, participate in the process of pulmonary vascular remodeling in patients with pulmonary hypertension and in animal models (2,(5)(6)(7)(8). For example, expression of EGF or its receptor EGFR are increased in animal models of monocrotaline-(MCT-) and hypoxia-induced pulmonary hypertension and in humans with pulmonary hypertension (8-10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several growth factors, including EGF, PDGF, and TGF-β1, participate in the process of pulmonary vascular remodeling in patients with pulmonary hypertension and in animal models (2,(5)(6)(7)(8). For example, expression of EGF or its receptor EGFR are increased in animal models of monocrotaline-(MCT-) and hypoxia-induced pulmonary hypertension and in humans with pulmonary hypertension (8-10).…”
Section: Introductionmentioning
confidence: 99%
“…For example, expression of EGF or its receptor EGFR are increased in animal models of monocrotaline-(MCT-) and hypoxia-induced pulmonary hypertension and in humans with pulmonary hypertension (8)(9)(10). Blockade of EGFR results in reductions in pulmonary pressure, right ventricular hypertrophy, and distal arterial muscularization in MCT-induced pulmonary hypertension (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two widely used small animal models of chronic pulmonary hypertension: exposure to chronic hypoxia (1, 2) and the "inflammatory" model of pulmonary hypertension in rats injected with the alkaloid monocrotaline (MCT) (3)(4)(5)(6)(7)(8)(9)(10). We have recently reported that chronic administration of platelet-activating factor (PAF) receptor antagonists prevents the development of pulmonary hypertension in both models (2,6,7), suggesting that the ether lipid PAF directly or indirectly is involved in the vascular remodeling and pulmonary hypertension in these animal models.…”
mentioning
confidence: 99%
“…Nitric oxide (NO), an endothelium-derived vasodilator, has also an antiproliferative action over vascular smooth musculature 14 , possibly connected to intracellular cyclic GMP generation. In fact, it has been considered that phosphodiesterase 5 enzyme (which degrades cyclic GMP) inhibitors could act on hypoxia-induced pulmonary vascular remodeling 15 .…”
Section: Cellular Proliferation and Matrix Changes In Pulmonary Vascumentioning
confidence: 99%